2022
DOI: 10.3389/fsurg.2022.922684
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Computational Analysis on the Effectiveness of Enhanced Recovery after Surgery in the Operating Room with Nursing

Abstract: ObjectiveIn order to better understand the relative surgical process, this work used a model-based computational analysis on the effectiveness of enhanced recovery after surgery (ERAS) in the operating room with nursing.MethodsA total of 360 surgical patients in the First Affiliated Hospital, Sun Yat-sen University, from the period June 2020 to March 2021, were randomly divided into two groups, namely, observation group and control group, with 180 cases in each group. Routine nursing was used in the control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…Hospitals and departments can provide targeted training in these aspects to improve the knowledge of nurses in the perioperative period with ERAS. The above results were similar to these of a previous study (Li, 2021), which reported that the correct rate of knowledge of preoperative bowel preparation was low among nurses.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hospitals and departments can provide targeted training in these aspects to improve the knowledge of nurses in the perioperative period with ERAS. The above results were similar to these of a previous study (Li, 2021), which reported that the correct rate of knowledge of preoperative bowel preparation was low among nurses.…”
Section: Discussionsupporting
confidence: 92%
“…Herein, Nurses with better familiarity with ERAS had a higher level of KAP, which can be because better familiarity is the result of repetition in learning and practice. The study of Li also found that nurses who had participated in standardized training or studied the guidelines of ERAS scored higher in KAP (Li, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[ 11 ] Indwelling deep vein catheterization and urinary catheterization were selected according to the surgical method and the patient systemic condition. [ 12 ] Deep vein catheterization and urinary catheterization were not indicated when the operation time was short and/or blood loss was limited during surgery. During surgery, more attention is paid to brain protection, body temperature management, and prophylactic antibiotics when the operation time exceeds 3 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Nursing interventions in the operating room as one of the most important parts of the ERAS protocol and have attracted much attention from ERAS study groups. [ 11 , 12 ] According to several studies, the conception of rapid rehabilitation under operating room nursing care of patients undergoing surgery can effectively decrease postoperative stress and potential complications, thus enabling patients to recover as quickly as possible. [ 11 , 13 ] Although conventional operating room nursing care can promote recovery to some extent, it has inherent drawbacks including a focus on the disease itself and the lack of psychological state assessment.…”
Section: Introductionmentioning
confidence: 99%